Canine adenovirus type 1 (CAdV‐1) in free‐ranging European brown bear (Ursus arctos arctos): A threat for Cantabrian population?. Issue 6 (20th September 2018) - García Marín, Juan F.; Royo, Luis J.; Oleaga, Alvaro; Gayo, Elena; Alarcia, Olga; Pinto, Daniel; Martínez, Ileana Z.; González, Patricia; Balsera, Ramón; Marcos, Jaime L.; Balseiro, Ana
Abstract: Canine adenovirus type 1 (CAdV‐1) is responsible for infectious canine hepatitis. The disease has been described in captive American black bear ( Ursus americanus ) and European brown bear ( Ursus arctos arctos ), with just one recently reported case in a cub of a free‐ranging brown bear ( Ursus arctos horribilis ) from Alaska. The aim of this work is to summarize findings related to presence and associated mortality of CAdV‐1 in 21 free‐ranging Cantabrian brown bears ( Ursus arctos arctos ) submitted to necropsy in Asturias and Castilla y León (northwestern Spain) from 1998 to 2018. On the basis of the anatomopathological findings and laboratory results three free‐ranging brown bears died due to infectious canine hepatitis, which is to our knowledge the first description of death due to this disease in free‐ranging bears in Europe. Gross lesions consisted of petechial haemorrhages and congestion in different internal organs, haemorrhagic fluid in internal cavities, friable and yellowish liver and thickening of gall bladder. Microscopic lesions were observed mainly in liver, kidney and brain and consisted of multifocal necrosis of cells with presence of basophilic intranuclear inclusions. Immunohistochemical (IHC) and real‐time polymerase chain reaction (qPCR) techniques were used to assess the presence of CAdV‐1 in paraffin‐embedded liver samples. Viral antigens were detected by IHC labelling within hepatocytes and Küppfer cells in the three animals. The presence of viral DNA was confirmed by qPCR in one of them. In order to evaluate the circulation of CAdV‐1 in brown bears, a retrospective study was performed using both IHC and qPCR techniques in 11 and 12 additional brown bears, respectively. An extra brown bear was found positive by IHC. This study shows that CAdV‐1 surveillance of brown bears and sympatric carnivores should be considered as major concern for the monitoring the population evolution throughout time in this endangered species.